The Influence Of Transformational Leadership And Work Facilities On Employee Performance At The Regional Office Of The Ministry Of Religion Of Gorontalo Province - Pantulu, Siti Nur Fadila; Igirisa, Irawaty; Isa, Rusli (Public Policy Journal, 2025)
Employee performance is an important factor in the success ofan organization, especially in the government sector. However, inpractice, various obstacles are still found that affect performance, such asa leadership style that is not optimal and limited work facilities. At theRegional Office of the Ministry of Religion of Gorontalo Province, anumber of performance indicators have not been achieved optimally,which shows the need to evaluate internal organizational factors. Thisstudy aims to determine the influence of transformational leadership andwork facilities on employee performance, as well as analyze whether workfacilities play a role as a mediating variable in the relationship betweenleadership and performance. The research uses a quantitative approachwith an associative descriptive method. Data was collected through aquestionnaire to 32 employees, and analyzed using the Partial LeastSquare (PLS) technique through the SmartPLS application. The results ofthe study show that transformational leadership does not have asignificant direct effect on employee performance. On the other hand,work facilities have a significant effect and transformational leadershipaffects employee performance through work facilities. This means thatdirection and motivation from leaders will only have an impact onimproving performance if they are supported by adequate work facilities.These findings confirm the importance of the role of work facilities insupporting leadership effectiveness. Therefore, organizations need toprioritize the management of work facilities as part of a comprehensiveand sustainable employee performance improvement strategy.